2015
DOI: 10.1021/acsmedchemlett.5b00084
|View full text |Cite
|
Sign up to set email alerts
|

BRD4 Structure–Activity Relationships of Dual PLK1 Kinase/BRD4 Bromodomain Inhibitor BI-2536

Abstract: A focused library of analogues of the dual PLK1 kinase/BRD4 bromodomain inhibitor BI-2536 was prepared and then analyzed for BRD4 and PLK1 inhibitory activities. Particularly, replacement of the cyclopentyl group with a 3-bromobenzyl moiety afforded the most potent BRD4 inhibitor of the series (39j) with a K i = 8.7 nM, which was equipotent against PLK1. The superior affinity of 39j over the parental compound to BRD4 possibly derives from improved interactions with the WPF shelf. Meanwhile, substitution of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
88
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(94 citation statements)
references
References 28 publications
6
88
0
Order By: Relevance
“…Soon after, two new studies (64, 65) identified more than a dozen kinase inhibitors that possess cross-reactivity towards BRD4 with nanomolar potencies, including the JAK2 inhibitor TG101209 and the PLK1 inhibitor BI2536 which is in Phase I/II Clinical trials for acute myeloid leukemia (AML) and non-small cell lung cancer (NSCLC). This finding has triggered the development of more potent dual BET/PLK1 inhibitors using a structure–activity relationship (SAR) study (66). Notably, LY94002 which has been routinely used to block PI3K activity was also recently shown to interact with BRD2–4 (67).…”
Section: Clinical-translational Advancesmentioning
confidence: 99%
“…Soon after, two new studies (64, 65) identified more than a dozen kinase inhibitors that possess cross-reactivity towards BRD4 with nanomolar potencies, including the JAK2 inhibitor TG101209 and the PLK1 inhibitor BI2536 which is in Phase I/II Clinical trials for acute myeloid leukemia (AML) and non-small cell lung cancer (NSCLC). This finding has triggered the development of more potent dual BET/PLK1 inhibitors using a structure–activity relationship (SAR) study (66). Notably, LY94002 which has been routinely used to block PI3K activity was also recently shown to interact with BRD2–4 (67).…”
Section: Clinical-translational Advancesmentioning
confidence: 99%
“…While previous studies of BET inhibitors have used cellular viability assays as a high‐throughput surrogate for cellular activity, this is less feasible for a recently reported class of compounds that can inhibit both BET proteins and selected kinase signaling proteins . This includes BI2536 that possesses dual activity against BET proteins and PLK1.…”
Section: Figurementioning
confidence: 99%
“…Included in this set are four compounds recently described by Chen et al. in similar in vitro BRD4 and PLK1 activity and cell viability assays ( 1/39 q , 3/39 p , 5/39 b , 7/39 a ) . Our data here largely corresponds with previously reported activity trends for these compounds.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…We found that MYC was downregulated and AKT3 was upregulated in these cells. BI 2536 and BI 6727 are dual inhibitors of both PLK1 and bromodomain containing 4 (BRD4) . The high concentration of BI 2536 represses MYC transcription by inhibiting BRD4, and AKT‐mediated phosphorylation of GSK‐3β at Ser‐9 represses GSK‐3β activity .…”
Section: Discussionmentioning
confidence: 99%